1978
DOI: 10.1017/s0021859600060020
|View full text |Cite
|
Sign up to set email alerts
|

A semi-micro dry-block and automated analyser technique suitable for determining protein nitrogen in plant material

Abstract: A dry-block digestion system suitable for the estimation of total protein nitrogen in plant material has been evaluated. The method was found to be as accurate as Kjeldahl flask digestion, required much less fume cupboard space and enabled samples to be dealt with in large batches through weighing, digestion and analysis. The batch size can be designed to be compatible with the autoanalyser capacity. These advantages result in more rapid analysis with less chance of errors and accidents. A 45 min digestion per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…aestivumL.) cultivars, HY320 (DePauw et al 1987) with high yield and low grain protein concentration and Neepawa (Campbell 1970) (Starr and Smith 1978) and total P using the indophenol procedure (Varley 1966 and 1986 due to reduction of grain production relative to pre-anthesis biomass production. Spiertz and Ellen (1978), while Tipples (1980) In a growth chamber study Campbell et al (198i) reported that an uu".ug"^of 60% of total N was assimilated by anthesis, a value somewhat lower than the averase 8l % found in this study.…”
Section: Methodsmentioning
confidence: 99%
“…aestivumL.) cultivars, HY320 (DePauw et al 1987) with high yield and low grain protein concentration and Neepawa (Campbell 1970) (Starr and Smith 1978) and total P using the indophenol procedure (Varley 1966 and 1986 due to reduction of grain production relative to pre-anthesis biomass production. Spiertz and Ellen (1978), while Tipples (1980) In a growth chamber study Campbell et al (198i) reported that an uu".ug"^of 60% of total N was assimilated by anthesis, a value somewhat lower than the averase 8l % found in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Small areas, 2.32 m 2 , were hand harvested on each cropped plot to determine straw and grain weight and their N concentrations. The grain and straw were dried to 708C, ground and analyzed for Kjedahl N (Starr and Smith 1978).…”
Section: Forty-year Crop Rotation Experimentsmentioning
confidence: 99%
“…Small areas (2.32 m 2 ) were hand harvested in each plot to determine N concentrations in the grain and straw. After air drying the hand samples to a moisture content of about 6%, they were ground and analysed for N concentration (Starr and Smith 1978). The N content of the grain and straw were corrected to a constant 13.5% moisture basis.…”
Section: Experimental Design and Crop Managementmentioning
confidence: 99%